Study on the influence of base shear distribution on the seismic response of base-isolated split-foundation structures - Yangyang Tang; Baolong Jiang; Yingmin Li; Shuyan Ji (Journal of Asian Architecture and Building Engineering)
Split-foundation structures with base isolation have multiple isolation layers due to their uneven foundation heights. This complexity adds challenges to the seismic isolation design of split-foundation structures. In this paper, two special parameters, namely the shear non-uniformity factor Φ and the ratio of shear non-uniformity factor Γ, were proposed. Response spectrum analysis and time history analysis on base-isolated split-foundation structures with varying Φ and Γ were conducted to investigate their seismic response and damping effect. The results indicate that Φ primarily affects the seismic response in the lower stories and the upper embedding story. When Φ is too small or too large, it results in an uneven isolation effect. Moreover, when the base shear ratio βz exceeds 0.5, the distribution of plastic hinges is significantly affected by the variations in Φ. Additionally, the story shear and story drift ratio of lower stories in the along-slope direction are generally greater than that of the corresponding story of the non-isolated structure. Therefore, in the seismic isolation design of the split-foundation structure, the base shear at different embedding ends should be reasonably assigned. Special attention should also be given to the adverse effects in the along-slope direction.